Silicon modifies C:N:P stoichiometry and improves the physiological efficiency and dry matter mass production of sorghum grown under nutritional sufficiency - de Carvalho, Jonilson Santos; Frazão, Joaquim José [UNESP]; de Mello Prado, Renato [UNESP]; de Souza Júnior, Jonas Pereira [UNESP]; Costa, Milton Garcia [UNESP] (Springer Nature, 2022)
Silicon (Si) may be involved in the modification of C:N:P stoichiometry and in physiological processes, increasing sorghum growth and grain production. The objective was to evaluate the effect of Si supply on C:N:P:Si stoichiometry, physiological response, growth, and grain production of sorghum. The experiment was carried out in pots with four concentrations of Si: 0; 1.2; 2.4; and 3.6 mmol L−1 in a completely randomized design, with six replicates. Physiological attributes and dark green color index were measured and grain and biomass production were determined. Posteriorly, the plant material was ground to determine silicon (Si), carbon (C), nitrogen (N), and phosphorus (P) contents in order to analyze C:N:P:Si stoichiometry. C:Si and C:N ratios decreased at all Si concentrations applied (1.2, 2.4, and 3.6 mmol L−1) and in all plant parts studied, being lower at 3.6 mmol L−1. The lowest C:P ratios of leaves and roots were observed at 3.6 mmol L−1 Si and the lowest C:P ratio of stems was observed at 1.2 mmol L−1 Si. Si concentrations were not significant for the N:P ratio of leaves. The highest N:P ratio of stems was observed at 3.6 mmol L−1, while the lowest N:P ratio of roots was observed at 2.4 and 3.6 mmol L−1. Regardless of photosynthetic parameters, the application of 1.2 mmol L−1 Si enhanced photosynthetic rate. The application of 2.4 and 3.6 mmol L−1 enhanced stomatal conductance and dark green color index. The mass of 1000 grains was not influenced by Si applications, while Si applications at all concentrations studied (1.2, 2.4, and 3.6 mmol L−1) enhanced shoot and total dry matter, not affecting root dry matter and grain production. In conclusion, Si supply modifies C:N:P:Si stoichiometry and increases physiologic parameters, growth, development, and grain production in sorghum.